Strategi Pengembangan Nelayan ALat Tangkap Jaring Insang Hanyut (Drift Gill Net) di Desa Datah Bilang Kecamatan Long Hubung Kabupaten Mahakam Ulu - Putra, William; Juliani, Juliani; Darmansyah, Oon (Journal of Fisheries and Marine Applied Science, 2024)
The research was conducted in 3 villages, namely Datah Ilir Village, Datah Bilang Ulu and Datah Billang Baru which are included in the Long Hubung District area, Mahakam Ulu Regency. It take place from January 2022 until May 2024. Datah collection was carried out using direct observation methods in the field and interviews with respondents based on questionnaires that were provided before the field survey. And the datah analysis method used is SWOT Analysis (Strength, Weakness, Opportunity, Threats). The results of this research indicate that the strategy for developing floating gill net fishermen is to utilize their strengths to open up existing opportunities. The IFAS (internal factor evaluation) value is 1.80 and the EFAS (External Factor evaluation) value is 1.41. So the recommended development strategy is quadrant I because the scores obtained by IFAS and EFAS are positive. The problem faced isthat many fishermen still use poison and electric shocks, and there is still a lack of guidance from the district government.